Macronyssus flavus - Orlova, M. V.; Klimov, P. B.; Orlov, O. L.; Smirnov, D. G.; Zhigalin, A. V.; Budaeva, I. V.; Emelyanova, A. A.; Anisimov, N. V. (Zenodo, 2021)
Macronyssus flavus (Kolenati, 1856) Dermanissus [sic] flavus Kolenati, 1856: 19. ? Dermanissus lobatus Kolenati, 1856: 20. Liponyssus lobatus .— Kolenati, 1856: 22; Porta, 1914: 481. Lepronyssus flavus .— Kolenati, 1858: 6; Fonseca, 1948: 306; Turk, 1953: 13; Bogdanov, 1953: 31. Lepronyssus lobatus .— Kolenati, 1858: 6; Turk, 1953: 13. Liponyssus flavus .— Hirst 1922: 791. Ichoronyssus britannicus Fonseca, 1948: 299 (synonymy by Radovsky, 1966). Ichoronyssus flavus .— Arzamasov & Kurskov, 1962: 203; Vshivkov, 1963: 324; Bregetova, 1953: 330; Morozova et al ., 1964: 162; Dusbábek, 1964a: 81; 1966: 44; Zemskaya, 1965: 316; Dubovchenko, 1968: 8; Pinchuk, 1970: 73; Mahnert, 1971: 926. Macronyssus flavus .— Evans et al ., 1961: 140; Radovsky, 1966: 94; 1967: 131; Juvara, 1967: 187; Beron, 1968: 159; Uchikawa, 1976: 841; Rybin, 1983: 357; Rybin et al ., 1989: 425; Baker & Beccaloni, 2006: 173; Haitlinger & Lupicky, 2008: 124; Radovsky, 2010: 56. Type locality: Czech Republic (“Böhmen, Mähren ”) (Kolenati, 1856). Type host: Nyctalus noctula (Kolenati, 1856). Material. N1 ex Nyctalus noctula from Akhshtyrskaya cave, 1-31 August 2001, leg. D.G. Smirnov; 2 MM, N1 ex Nyctalus noctula from NP “Nurgush”, 24 June 2006, leg. D.G. Smirnov; 2 FF, 9 N1 ex N . noctula from Mordovskiy State Natural Reserve, 21 June 2016, leg. D.G. Smirnov; 6 FF, 3 MM, 5 N1 ex N . noctula from Shaytan-Kazak, 19 May 2019, leg. D.G. Smirnov, A.M. Lukyanenko; N1 ex Pipistrellus pipistrellus from neighborhood of Khasavyurt town, 20 May 2019, leg. D.G. Smirnov, A.M. Lukyanenko; 18 FF, 10 N1, N2 ex N . noctula from State Nature Reserve “Samarskaya Luka”, 1-31 June 2006, leg. D.G. Smirnov; 6 FF, M, N2 ex N . leisleri from SNR “Samarskaya Luka”, 1-31 June 2006, leg. D.G. Smirnov; 42 FF, 2 MM, 203 N1, 7 N2 ex N . lasiopterus from SNR “Samarskaya Luka”, 25 July 2006, leg. D.G. Smirnov; 5 FF ex Myotis daubentonii from SNR “Samarskaya Luka”, 1-31 November 2005, leg. D.G. Smirnov; F, M ex Myotis daubentonii from SNR “Samarskaya Luka”, 1-31 July 2006, ...